Falla Estructural En La Esquina Del Muro Suroccidental De Cerramiento Perimetral Del Conjunto Pentagrama De La Ciudad De Bogotá (2024)
The realization of this work allowed the application of the knowledge acquired during the Civil Engineering career at the Universidad Antonio Nariño, through the practical study of the pathology of the object of study, therefore, this document presents the analysis and research conducted to the structure of the southwest corner of the perimeter enclosure wall of the Conjunto Residencial Pentagrama P.H. in the city of Bogotá D.C.